Study on Structural Deflection in Attitude Maneuvers of Flexible Satellite Equipped with Fuel-Efficient Input Shaper - Parmana, Setyamartana (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2015)
Input shaping technique can successfully suppresses residual vibration in slew maneuvers of flexible systems. This paper studies transient structural deflections of flexible satellite during attitude maneuvers controlled using input shaper. The satellite consists of a rigid main body and two symmetrical flexible solar panels. The equations of motion of the satellite are derived using Lagrange’s formulation, and elastic motions of flexible structures are discretized following the finite element method. The attitude maneuvers areequipped with on-off constant amplitude inputs. For fast maneuver, the satellite has poor accuracy after the maneuver. To resolve this issue, input shaper is applied to maneuver the satellite. Various fuel-efficient shaped inputs are studied in order to conclude the relation of input shape and transient maximum deflection resulted.